Inauguration Speech of the school year 1993 of the School of Library, Documentation and Information - Conejo Solera, Carlos (1993)
Speech given by the Director of the Computer Center of the Universidad Nacional el ING. Carlos Conejo Solera on the Inauguration of the 1993 School of Librarianship, Documentation and Information Course.